Evaluation of a system for enhancing mobile telephone communication for people with hearing loss. (3rd July 2019) - Moore, Brian C. J.; Shaw, Sally; Griffiths, Stephen; Stone, Michael A.; Sherlock, Zak
Abstract: Objective: To evaluate a system – "the service" – designed to improve mobile telephone communication for people with hearing loss. Design: Each participant registered online and took an online hearing test using their own mobile telephone held in the position of their choice. The test assessed the combined effects of the telephone, the hearing loss of the participant and the hearing aid of the participant (if worn). The results were stored as a "hearing profile" and used to set up frequency-dependent amplification and multichannel amplitude compression. The signal processing was performed in the telephone network and applied to all calls of the participant. Participants completed four questionnaires about their listening experiences using the telephone, one before using the service, two while using the service and one after using the service. Also, the ability to understand speech was measured using challenging sentences. Study sample: Fifty-three participants with varying degrees of hearing loss. Results: The great majority of participants indicated that call clarity was improved and that listening difficulty was reduced when using the service. Speech intelligibility scores were significantly improved when using the service. Conclusions: The service appears to be effective in improving phone communication for people with hearing loss.